A Fault Tolerant Approach to Anti-windup Gain Implementation - Acuña-Bravo, Wilber; Ríos-Bolívar, Addison (Revista Técnica da Faculdade de Engenharia da de Zulia, 1970)
A new approach to anti-windup gain implementation is shown. To this aim, a fault detection and isolation system is used. Actuators saturation is taken as a failure in the control system, which is detected and isolated by means of a fault detection filter bank (multifiltering), whose residuals are used to carry out the saturation compensation. Under this framework, a fault tolerant control system to this particular fault is achieved, which presents robustness proprieties with respect to changes in the actuators performance. Fault detection filters design is done, by means of robust optimal control in H2/H[1] techniques, based on linear matrix inequalities. Some numerical examples are shown in order to verify the proposed approach properties.